Prospective study comparing the safety and efficacy of totally tubeless percutaneous nephrolithotomy vs standard percutaneous nephrolithotomy - Vig, Mukta; Vig, Vishal; Nagi, Gurinderjit S.; Suchak, Suraj; Goyal, Subhash (International Journal of Research in Medical Sciences, 2016)
Background: To evaluate the feasibility and safety of totally tubeless percutaneous nephrolithotomy (PCNL) Vs standard PCNL. Methods: From August 2014 to January 2016, 66 patients underwent PCNL in our institute. Of this group, 35 patients underwent traditional nephrostomy drainage following PCNL. A tubeless procedure was performed in the remaining 31 patients. These groups were compared with respect to age, stone burden, intraoperative events, postoperative pain, analgesic requirements, soakage, postoperative change in hemoglobin, hospitalization time and complication rates. Results: Two groups were comparable with respect to age, stone burden (2.03 cm Vs. 2.12 cm) and intraoperative events. The mean pain score (day2 - 4.95 vs. 2.95) (day3 - 4.33 vs. 1.44) and analgesic requirement (mg diclofenac) (day2 - 140.22 vs. 65.31) (day3 - 124.44 vs. 43.89) was significantly less for group 2 on day 2 and 3. There was significant problem of soakage from nephrostomy tract in group 1. Patients in group 2 returned faster to normal activities but there was no difference found in drop in hemoglobin, complication rates even in subset of patients with large stone burden. No patient required readmission in the follow-up for pain, obstruction or infection in group 2. One patient developed urinoma which resolved conservatively Conclusions: In selected cases totally tubeless PCNL is feasible and safe.